Anodization of Aluminium Alloys in Hydrofluoric Acid and Sulfuric Acid for Space Applications - Somasundaram, Soniya; Murali Krishna, P. (Asian Journal of Chemistry, 2022)
Present work demonstrated the development of a typical solar reflector coating by optimizing the bath parameters for an anodizing process on aluminium 2024 alloy. This evidently explains the pre-cleaning as well as optimization of the bath parameters for the development of solar reflector anodic film on aluminium alloys. The electrolytic bath for anodization consists of concentrated sulphuric acid and hydrofluoric acid. The anodization parameters such as solution temperature, process time and current density were optimized in order to achieve an anodic film of 10-12 μm thickness on the aluminium surface based on α/ε ratio, [solar absorbance (α) and thermal emittance (ε)] with a low solar absorbance (< 0.20) and high thermal emittance (> 0.80). The chemical analysis of the surface coating has been done by energy dispersive X-ray spectroscopy (EDS) and microstructure analysis by scanning electron microscopy (SEM). The finalized anodic film was compared with the sulphuric acid and chromic acid anodized surface. The average breakdown voltage of the solar reflector specimens coating was 355 V, which is higher than sulphuric acid anodized and chromic acid anodized samples.